Critical evaluation of measured line positions of 14N16O in X2П state. (April 2018) - Sulakshina, O.N.; Borkov, Yu.G.
Highlights: The results of critical evaluation of measured rotation-vibration line positions of 14 N 16 O in the X 2 П state are presented. The analysis was carried out using the fundamental Rydberg-Ritz combination principle, for the available experimental data. As a result, the precise set of experimental energy levels of NO molecule in the interval 0–35, 886 сm −1 were obtained. Abstract: All available line positions for unresolved and resolved Λ-doublets of the 14 N 16 O molecule in the X 2 П state were collected from the literature and tested using the RITZ computer code. These data have been critically analysed and used to obtain the most complete set of 1789 experimental energy levels of unresolved Λ-doublets covering the 0–35, 866 cm −1 interval. A set of 425 experimental energy levels of resolved Λ-doublets covering the 0–5957 cm −1 interval for two states 2 П1/2 and 2 П3/2 also have been obtained. These levels together with calculated correlation matrix can be used to generate the precise list of transitions with confidence intervals. Comparisons with the HITRAN as well as with Amiot calculations are discussed. The systematic shift between experimental energy levels of unresolved Λ-doublets and those calculated by Amiot for 2 П3/2 state was found. The same systematic shift for transitions frequencies of unresolved Λ-doublets in forbidden subbands 2 П1/2 ↔ 2 П3/2 is also established in the HITRAN database. Comparison of the RITZ energy levels with calculated energy levels by Wong at al. was also done. It was found, that experimental RITZ energy levels for resolved Λ-doublets of 14 N 16 O coincide with those calculated by Wong at al. within experimental uncertainties.